Campus Canopy, 1948-12-11 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1948)
"Oh Come, All Ye Faithful" -- First Dance In '49 To Be January 8 -- Artist Series To Present Vienna Choir Boys Jan 20th -- Christmas Festivities Highlighted By GWC's Traditional Yuletide Service -- Dean Tate Speaks At Last Assembly of Fall Quarter -- Family Dinner Served at 6:30
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals